Financial Feasibility Analysis and Cash Flow Projection in Diagnostic X-ray Screening Business Model - Yus Dakaria; Rhian Indradewa; Sukmo Hadi Nugroho; Unggul Kustiawan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
Financial planning is an important foundation in establishing technology-based health services such as the X-ray Screening System Clinic. This study aims to develop a comprehensive financial plan that includes initial investment estimates, cash flow projections, and financial feasibility analysis using the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) methods. Using a quantitative-descriptive approach, data was collected through market studies, expert interviews, and benchmarking of radiology clinic operating costs. The results show that with a target service volume of 1,000 patients/month, the clinic's investment of Rp750 million can be recovered within 2 years with an IRR of 28.5% and a positive NPV. This study provides a strategic basis for investors or management in making financial decisions on the establishment of diagnostic clinics